Vocal Musical Practice and Oral Transmission in Tunisia: Forms and Socio-Cultural Representations (The Region of Kebili) - Aida NIATI (Turath, 2025)
This study explores the intrinsic link between musical traditions and their socio-cultural environments, emphasizing how geographic contexts and ritual practices shape and inform vocal expressions. Focusing on the region of Kébili in southern Tunisia, the article examines specific local manifestations of vocal performance—namely the voice of El Jourrad, the voice of El Bourrach, and the voice of El Akrmi. Through this case study, the paper aims to analyze the communicative and symbolic mechanisms underlying these vocal practices, shedding light on their roles within the region’s intangible cultural heritage.